GERD outcome after bariatric surgery A protocol for systematic review and meta analysis - Abdel-Naser Elzouki (9376853) (2020)
Background/Aim Obesity is associated with increased incidence of gastroesophageal reflux disease (GERD), and it has been suggested that GERD symptoms may be improved by weight reduction. However, various patterns of bariatric surgery may affect symptoms of GERD due to the changed anatomy of stomach and esophagus. The aim of this systematic review and meta-analysis is to analyze the effect of bariatric surgery on GERD. Materials and methods A systematic literature search was performed using PubMed, EMBASE, and the Cochrane Library from January 2005 to January 2019, combining the words obesity, gastroesophageal reflux with different types of bariatric surgery and weight loss. The methodological quality of randomized controlled trials and non-randomized controlled trials published in English and have at least 1-year follow-up data were included and assessed by Cochrane Collaboration’s tool for assessing risk bias and Newcastle–Ottawa scale. Only clinical trials were included, and case series or case reports were excluded. Results We anticipate that our review will provide the exact estimates of the burden and phenotype of GERD among patients that have undergone bariatric surgery. Conclusion GERD may improve in obese patients who underwent laparoscopic sleeve gastrectomy (LSG); however, the most favorable effect is likely to be found after Roux-en-Y gastric bypass surgery. Prospero registration number: CRD42018090074. Abbreviations GERD = gastroesophageal reflux disease, LSG = laparoscopic sleeve gastrectomy, NMA = network metaanalysis, PRISMA-P = Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. Other Information Published in: Medicine License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1097/md.0000000000019823